2021
DOI: 10.1111/1751-7915.13968
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture modulates the intestinal microecology to improve intestinal motility in spinal cord injury rats

Abstract: Spinal cord injury (SCI) is a disease involving gastrointestinal disorders. The underlying mechanisms of the potential protective effects of electroacupuncture (EA) and 5-hydroxytryptamine (5-HT) system on SCI remain unknown. We investigated whether EA improves gut microbial dysbiosis in SCI and regulates the 5-HT system. 16S rDNA gene sequencing was applied to investigate alterations in the gut microbiome of the rats. Faecal metabolites and the expression of the 5-HT system were detected. EA and faecal microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…In particular, we identified a significant and region-specific decrease in the mucosal concentration of ACh in the right colon and lower 5-HT concentration in the left colon as compared to that of CTs. A similar reduction of 5-HT was reported in a model of rat SCI 38 . In addition, we also observed an increased SERT mRNA expression, which could reduce the bioavailability of 5-HT and further contribute to constipation in SCI patients.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In particular, we identified a significant and region-specific decrease in the mucosal concentration of ACh in the right colon and lower 5-HT concentration in the left colon as compared to that of CTs. A similar reduction of 5-HT was reported in a model of rat SCI 38 . In addition, we also observed an increased SERT mRNA expression, which could reduce the bioavailability of 5-HT and further contribute to constipation in SCI patients.…”
Section: Discussionsupporting
confidence: 86%
“…However, the ability of IL-1β to regulate TPH1 mRNA expression remains unknown. The importance of this altered 5-HT in gastrointestinal motility disturbances is also further highlighted by the fact that therapeutic approaches for improving motility in preclinical models of SCI, such as electroacupuncture 38 or microbiota transfer 39 , are associated with the restoration of 5-HT levels. Moreover, 5-HT4R agonists such as prucalopride 40 demonstrably improve colonic transit time in SCI patients.…”
Section: Discussionmentioning
confidence: 99%
“…When treating SCI, it was discovered in a therapeutic study that some therapeutic techniques, including melatonin, electroacupuncture, and minocycline, also regulate the microbiota (120,121). This might offer a fresh concept and treatment objective for SCI.…”
Section: Microbiomicsmentioning
confidence: 99%
“…Spinal cord injuryinduced gut dysbiosis could be alleviated also due to melatonin treatment [76] and by treatment with a fecal transplant as well [77]. Furthermore, electroacupuncture modulates the intestinal microecology to improve intestinal motility in spinal cord injury rats [78]. Moreover, Schmidt et al [79] have showed that that minocycline augments inflammation and anxiety-like behavior following SCI in rats through action on the gut microbiota.…”
Section: Promising Modulation Strategies Of Sci-induced Microglial Pl...mentioning
confidence: 99%